(untitled) (Vietnam Journal of Community Medicine, 2022)
Introduction: Evidence-based practice is a combination of the best evidence combined with the skills, clinical experience of the nurse and the values of the patient, demonstrated through correct, effective practice with clinical evidence, best evidence and clinically relevant. Evidence-based practices to improve quality of care and patient safety. Target: Determine the mean score of the information sources used as evidence and the relationship between the information sources and the general characteristics of the sample in applying evidence to nursing practice. Methods and materials: A descriptive cross-sectional study on 169 nurses with college degrees or higher who are working at Quang Nam General Hospital from October 2020 to April 2021. Information was collected through a self-completed questionnaire. Results: The study showed that the information from colleagues and information sources belongs to personal experience and has the highest average score of 4.02±0.46, and 3.94±0.4, respectively; information from outside has a mean score of 3.64 ± 0.53. Information sources from hospital sources were 3.42±0.47; Information sources from research evidence were reported with the lowest mean score of 3.16±0.43. Found a statistically significant difference (p<0.05) between education level and using information sources from research evidence. Between age groups, personal experience with the source of information belongs to personal experience. Conclude: Research shows that the highest average scores belong to information from colleagues and information sources from personal experience. There was a statistically significant difference between education level, age group and personal experience with the use of information sources from research evidence, and information belonging to personal experience. Thereby providing information on the correlations affecting the source of nursing information used in practice.